Effects processors for electric guitar: a physical approach to teaching wave theory - A.W.D. Costa; J.P.M. Braga (Revista Brasileira de Ensino de Física)
This work explores the intersection of music and physics through the use of signal and audio processors on the electric guitar, focusing on wave physics and timbre manipulation. It posits that physics is crucial in designing and operating electric guitar signal processors by understanding wave phenomena. The research emphasizes the need for a thorough understanding of the physical processes behind sound effects to inspire innovative music creation besides demonstrating how the relationship between frequencies, amplitudes, and phases of sound waves can be creatively and consciously explored, promoting a deeper understanding of electric guitar effect processors. This physical approach advances knowledge in acoustics, sound engineering, and wave physics, expanding creative possibilities in music. The methodology involved assessing sound effects, such as distortion, chorus, flanger, wah-wah, and delay, applied to the original signal, captured from an electric guitar and analyzed in MATLAB to study its waveform. The results demonstrated how these effects alter the signal’s shape and frequency spectrum, underscoring the importance of wave fundamentals in sound effects creation and enhancing understanding of sound wave transformations.